Not "Forsworn with Pink Ribbons": Hannah More, Thomas De Quincey, and the Literature of Power - Roberts, Daniel (Romanticism on the Net, 2002)
AbstractDe Quincey's conception of the literature of "power" as opposed to that of "knowledge," has proved to be one of the most influential of romantic theories of literature, playing no small part in the canonization of Wordsworth. De Quincey's early acquaintance with the Lyrical Ballads was made through the Evangelical circles of his mother, who was a follower of Hannah More and a member of the Clapham sect. In later years, however, De Quincey repudiated his early Evangelical upbringing and wrote quite scathingly of the literary pretensions of Hannah More. This paper attempts to uncover the revisionary nature of De Quincey's later reminiscences of More and to indicate thereby the covert influence of Evangelical thinking on his literary theorizing. Far from absolving literature of politics, however, colonialist and nationalist imperatives typical of Evangelical thinking may be seen to operate within the spiritualized and aesthetic sphere to which literary power is arrogated by De Quincey.